El concepto de amor en Hannah Arendt - Fernández López, Daniel (Foro Interno, 2016)
In her doctoral dissertation Hannah Arendt examined the question of love in Saint Augustine of Hippo. The Algerian bishop emphasized love of one’s neighbor as a way of meeting God, as his desire was the civitate Dei. Fifteen centuries later, Arendt secularized the concept and developed a political theory based on love of the world, of life and of men. For this purpose, she developed several concepts, including action, natality and politics, which in turn require elements such as plurality, novelty or freedom. Therefore, love is a key concept in her work, even though she stated that this was an apolitical and antipolitical force.